Identification and characterization of small organic compounds within the corona formed around engineered nanoparticles. Issue 6 (4th May 2018) - Pink, Mario; Verma, Nisha; Kersch, Christian; Schmitz-Spanke, Simone
Abstract : The biological identity of nanoparticles depends on the organic compounds bound to the surface; however, compounds other than proteins are largely uninvestigated. This study highlights the presence of unique compound profiles within the corona of the tested nanoparticles. Abstract : The dynamics between biomolecules and nanoparticles, the so-called nanoparticle corona, is of great interest. It is proposed that it is the presentation of the biomolecules on the surface rather than the particles themselves which is the actual cause of numerous biological responses. While in recent years many advances have been made in analyzing the protein corona, information about other small organic components present in the corona, i.e. the organic corona, is missing although it may have a considerable influence on the biological effect of nanoparticles. The paper presented here is part of a wider research effort aimed at understanding the behavior of nanoparticles and the formation of the organic corona, in particular, of engineered nanoparticles (copper oxide, titanium dioxide, zinc oxide, zirconium dioxide, and carbon black). The particles were suspended in two different biological fluids (cell culture medium and simulated lung fluid), and the formed organic corona was then analyzed using an untargeted metabolomics approach. Several in silico analytical approaches were applied on the obtained data to assess and interpret changes in the composition of the organic corona. Principal component analysis (PCA) and enrichment analysis pointed towards amino and carboxylic groups as important determinants in the binding of the small organic compounds to the nanoparticle surface. Moreover, the biological enrichment analysis associated the identified small organic compounds with the antioxidant system and ammonia metabolism.